Radionuclides and trace elements of red palm oil, water and soil from palm plantations - Olafisoye, Oladunni Bola (Cape Peninsula University of Technology, 2021)
The oil palm plantation and produce from the oil palm tree has provided employment and economic maintenance of life and existence for numerous countries all over the globe. The virgin palm oil has a good percentage of vitamin A, C and E. Having discovered that metals and radionuclides may be persistent detrimental, non-biodegradable and accumulate in the eco-system; major concerns of regulatory agencies in countries worldwide are the susceptibility of metals and radionuclides due do the deregulation of disposal of wastes and effluents in the environment. Based on this fact, the effect of the uptake of metals and radionuclides from soil, groundwater, and its translocation to the oil palm fruit was determined on fifteen independent oil palm plantations in Nigeria. Areas in the Southern part of Nigeria where oil palm is greatly cultivated include the states of Edo, Enugu, Delta, Akwa Ibom, Ondo, Ekiti, Kogi, Oyo, Osun, Ogun, and Lagos. Soil, water, and palm oil were collected from fifteen major sites from areas in Nigeria. Sampling was performed in the dry season of October 2012 to April of 2013 using random and grab sampling methods. The solutions and reagents used for all analysis were analytical grade. Reference materials were used for the validation of the analytical methods when using the instruments. The Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) equipped with radial viewed plasma was used in the research for the determination of total metal concentrations in soil, water, and palm oil and metal speciation in soil samples. The highest concentration of metals recorded was for Lead (Pb) (0.090-10.29 mg/L) and the lowest for Cadmium (Cd) (0.119-0.391 mg/L) on all the ground water sampled on the fifteen independent sampling locations. The procedure for the determination of the bioavailability and bio-accessibility of metals in soil in this study was the BCR three-step sequential extraction. The concentration of metals in palm oil and the risk assessment of metals from palm oil to soil were also evaluated. Micro emulsion technique was used as sample preparation method for the extraction of the metals in virgin palm oil from the matrix. The concentrations of metals found in the oil samples analysed on all fifteen sampling locations ranged between 0.006 mg/L in Ubiaja plantation and 161.576 mg/L in Benin City plantation respectively. Sn metal recorded high concentration in Benin City plantation and Pb metal recorded a low concentration in Ubiaja plantation. The study revealed that the Daily Intake of Metals (DIM), Health Risk Index (HRI), and Accumulation Factor (AF) values were above unity in most of the plantations and this is suggestive of risk to the food chain. The concentrations of metallic elements were rather high in most samples, hence the oil is best suitable for use as fuel or raw material for the chemical industry. Most of the palm oil analysed for metallic elements were not suitable for human consumption, and anthropogenic pollution of the soils may be identified as the source of contamination. The concentration of the metals found in the study was compared with quality standard for metals in soil, water and food set by the World Health Organization. Other aspect of the study focused on the oxidative stability coupled with the cheap monetary cost of the virgin palm oil as one of the best cholesterol-free oils especially when blended to prolong shelf life. Virgin palm oil undergoes rancidity during storage and this affects the shelf life and aesthetics of the palm oil. Oil palm plantation farmers may add synthetic phenolic antioxidants to the palm oil during storage for preservation and for longer shelf life of the palm oil. Virgin palm oil was analysed for synthetic phenolic antioxidants by Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) coupled with an Ultraviolet /Visible (UV-Vis) detector. Hexane and acetonitrile were employed as solvents for the extraction procedure. Qualitative and quantitative analysis was performed on the oil to determine the concentration of Butylatedhydroxytoluene (BHT), butylatedhydroxyanisole (BHA), propyl gallate (PG) and 2- ethylhexyl 4-methoxycinnamate (EEMC). The limits of detection for BHA, BHT, EEMC, and PG were 0.041, 0.057, 0.06, and 0.03 mg/L respectively. Limits of quantification for BHA, BHT, EEMC and PG were also 0.56, 0.49, 0.05 and 0.04 mg/L respectively. None of the synthetic antioxidants was detected in the real samples under investigation. This was an indication that local farmers probably preserved the oil samples prior to storage by traditional methods. Soil, palm oil, and water were assessed in another aspect of the study for radionuclide activity concentrations on the fifteen sampling locations in the southeast, southwest and south south regions of Nigeria using the Hyper Pure Germanium Detector (HPGe). The radioactivity concentrations of 238U, 232Th and 40K were obtained from averaging the radioactivity concentrations of their respective progenies. The activity concentrations of 40K from soil depth of (0 – 15 cm) ranged from 187.4 – 514.4 Bq/kg. The activity concentrations of 238U from soil depth of (0 – 15) cm ranged from 2.328 - 6.571 Bq/kg and the activity concentrations of 232Th from soil depth of (0 - 15 cm) ranged from 1.509 - 6.121 Bq/kg respectively. The activity concentration of palm oil for 40K, 238U and 232Th ranged from 122.3 -968.0, 1.240 - 6.651 and 1.199 - 8.061 BqL-1 respectively. The annual effective dose and cancer risk in water polluted with Naturally Occurring Radioactive Materials (NORM) was investigated in the water as the ground water in the community is used as a source of drinking water and for domestic use. The activity concentration of 40K, 238U and 232Th were discussed and the annual effective dose for different age groups and cancer risk were estimated in the ground water samples. Activity concentration of 40K (Bq/L) were least in Okitipupa plantation (171.7 ± 0.01 Bq/L) and the highest activity was recorded in Ago-Emokpae plantation (468.9 ± 0.01 Bq/L) respectively. The activity concentrations of 238U (Bq/L) ranged between 1.611 ± 0.01 Bq/L – 5.750 ± 0.01 Bq/L and the concentrations were least in Ikire plantations and highest in Ago-Emokpae plantations respectively. Activity concentrations values (Bq/L) for 232Th in the ground water was highest in Ikire plantation (9.619 ± 0.26 Bq/L) and lowest in Apoje plantation (1.554 ± 0.62 Bq/L) respectively. The values for the Annual Effective Dose Estimation (E) (mSv/y) for 40K, 238U and 232Th reveal that E for 40K was highest in infants, children, and adults in this order; 3.51 × 10-4, 8.21 × 10-4, and 11.72 × 10-4 at W4 plantation respectively. Lowest values of E (mSv/y) were recorded in the same order at W12 plantation respectively as 1.29 × 10-4, 3.01 × 10-4, and 4.29 × 10-4). EDW values (mSv/y) for 232Th were negligible at W1 and W12 plantations. Highest and lowest values were recorded as 6.49 × 10-4 (W9); 9.76 × 10-4 (W9) and 9.17 × 10-4 (W2) for infants, children, and adults respectively. Lowest values of 232Th E values (mSv/y) in the sampled ground water were recorded (1.12 × 10-4, 1.68 × 10-4, and 1.12 × 10-4) for infants, children, and adults in W5 and W9 plantations respectively. The radionuclide 238U recorded E values (mSv/y) in the range of 0.77 × 10-4 mSv/y – 11.06 × 10-4 mSv/y, 1.04 × 10-4 mSv/y– 16.10 × 10-4 mSv/y and 2.25 × 10-4 mSv/y– 8.05 × 10-4 mSv/y for infants, children, and adults respectively. The values were generally low for infants. Radionuclide 232Th was not detected in Abak and Nsukka plantations. The calculation of cancer risks based on the radium isotopes ranges from 5.91 × 10-4 to 21.10 × 10-4 for 226Ra. For 228Ra, the values were from 5.87 × 10-4 to 1.64 × 10-4. Mean estimations were calculated as 26.25 × 10-4 and 3.891 × 10-4 for 226Ra and 228Ra respectively. Translocation Factor (Tf) in the all pressed virgin palm oil was greater than unity/very close to unity. The estimation of the assessed annual effective dose in drinking water for all the individual populations were below the recommended reference value of 0.1 mSv resulting from a year intake of drinking water in accordance with the WHO, IAEA and UNSCEAR regulated guideline values. The mean values for 226Ra and 228Ra obtained in this study for both isotopes were 3.891 × 10-4 and 26.25 × 10-3 for 226Ra and 228Ra respectively. The mean estimation of the radiological cancer risk for radium isotope for both 226Ra and 228Ra in this study is acceptable within the guideline limits of 1 × 10-4 to 1 × 10-6. The values obtained for soil samples were lesser than the worldwide values for soils in the region. None of the soil samples exceeded the permissible levels of 370 Bqkg-1 for radium equivalent recommended by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). Other radiological hazards in terms of Internal and External hazard indices and Representative hazard index in the soils were determined and found to be within safe limits.
Thesis (DPhil (Chemistry))--Cape Peninsula University of Technology, 2021
Keywords: Palm oil --Analysis; Radioisotopes; Trace elements; Trace and toxic metals; ICP-OES; HPLC; HPGe; Environmental pollution; Synthetic phenolic antioxidants; NORM; Radionuclide concentration